(untitled) (Jurnal Bahasa, 2023)
Geolinguistics combines geography and linguistics, and uses Geographical Information System (GIS) technology to map and find a language’s dialect boundary accurately. The Malay dialect in the state of Penang, which borders the states of Kedah, Perlis and Perak, will use this GIS technology to find the lexical variants that make up the various dialects of the state. Thus, this study will identify the use and spread of the lexical variations of "kapal", "kuih" and "panas", as well as generate the isogloss and choropleth mapping of these lexical variations in the state of Penang using the GIS application. This Geolinguistics study begins with the collection of lexical data made through field research in 27 villages throughout the districts of Penang state. The number of villages is small because Penang state is small. A total of 123 respondents from the old and young generations were questioned. This study has proven that the lexical variants of "kapal", "kuih" and "panas" are different. These variants have helped to discover new dialects, namely the Penang, Kedah and Patani Sik dialects, and mark this spread more accurately. Keywords: Geographical Information System (GIS), Penang dialect, choropleth, Kedah dialect, Patani Sik dialect, isogloss Full text: PDF